Analisis Faktor-Faktor yang Berpengaruh terhadap Customer Satisfaction pada Aplikasi Mobile Health - Amalia Ramadhina Ghaisani; Alim Setiawan Slamet; Amzul Rifin (Jurnal Manajemen dan Organisasi, 2024)
The COVID-19 pandemic has brought positive changes to the digital health industry in Indonesia. Kimia Farma Mobile is a mobile health application that offers comprehensive features for its users. The difference in ratings on Google Play Store and Apple App Store can influence trust (brand trust) and customer satisfaction with this application. The quality of electronic services, such as application interface, delivery quality, and transaction security, is increasingly crucial in influencing customer evaluations and ratings. Therefore, this research aims to analyze the factors influencing customer satisfaction with this application. The research was conducted quantitatively online through Google Form. The sampling method used convenience sampling and was analyzed using Structural Equation Modeling-Analysis Moment of Structural (SEM-AMOS). The research findings indicate that e-service quality significantly affects brand trust and customer satisfaction. This suggests that to improve brand trust and customer satisfaction, the mobile health application should be user-friendly and secure. Furthermore, brand trust significantly influences customer satisfaction. This implies that to enhance customer satisfaction, the mobile health application should provide educational and accurate information and offer customer guarantees.